Conservation of migratory bird in Malaysia and the law / Fatin Nabilah Abu Bakar…[et al.] - Abu Bakar, Fatin Nabilah; Rozlan, Najihah; Sharer, Najwa; Azman, Shahrina Noor; Zainal Abidin, Siti Sarah (2010)
This research looked at the conservation of the migratory birds in Malaysia and the law. The method used for this research is qualitative in nature. Malaysia has become a migration route for the migratory birds to stop by. Along the way of migration there are certain obstacles such as habitat destruction due to unsustainable development which incurred risk to the migratory birds and give the result of declines. In Malaysia, the law that governs migratory birds is the Protection of Wildlife Act 1972 (Act 76) only. Nevertheless, this Act does not give sufficient protection to the migratory birds. Thus, there is a need to amend the law in the current Protection of Wildlife Act 1972 (Act 76). It is important to conserve the migratory birds since biodiversity has been duly affected due to the imbalance of ecosystem. Moreover, the conservation of migratory bird is important as it would benefit a country in the sense of making profits and eco-tourism. The result of this research suggest that it is unfeasible to have a specific law to protect the migratory birds since the provisions in the Protection of Wildlife Act 1972 (Act 76) have clearly stated the aspirations in conserving these birds. However, several provision in the Act should be amended based on the current development by the societies in Malaysia and its realization towards a better sustainable living for the future generation.